Savings Bank Dividends (Quarterly Journal of Economics, 1889)
Savings Bank Dividends Get access The Quarterly Journal of Economics, Volume 3, Issue 2, January 1889, Pages 211–212, https://doi.org/10.1093/qje/3.2.211 Published: 01 January 1889